Analysis of a mock-up of a new sustainable easy-assembling modular arch. (June 2019) - Diaferio, Mariella; Dassisti, Michele; Foti, Dora; Vacca, Vitantonio
Abstract: Sustainability of buildings and constructions is almost a mandatory feature nowadays. New low-cost solutions are quite often pursued for increasing the structural and aesthetic quality of the manufactured units. This paper discusses a new idea of a modular component easy-to-assemble for low-cost structural arches on site, mainly for civil building applications. The related producibility issues are also discussed by presenting an appropriate manufacturing process able to propose a modular technology that could be easily implemented at industrial level, thus widening the use of easy-to-mount arches for civil buildings. The new concept of dimension stones, the different and appropriate use of materials may allow the reduction of resource consumption and assure the sustainability of the arches according to the proposal here discussed. The idea of a new assembled modular arch is here supported by scientific and technical evidences to show the potentialities for its use in real applications. The prototype of this modular arch has been subjected to static experimental tests whose results are discussed also by means of a numerical model able to predict the actual behaviour.